A synergetic framework for green and lean manufacturing practices in SMEs: Saudi Arabia perspective - Abualfaraa, Wadhah; Almanei, Mohammed; Kaur, Rashmeet; Al-Ashaab, Ahmed; McLaughlin, Patrick; Salonitis, Konstantinos (MDPI, 2023)
Manufacturers are urged to improve their sustainability performance, in terms of keeping the balance among economic, environmental, and social performances. Nevertheless, top managers and company leaders tend to complain that it is not possible to implement greener solutions without large investments. In this context, the well-known lean manufacturing approach, mainly focused on waste reduction, has come to be viewed with a renewed interest towards improving not only economic but also environmental and social aspects. Unfortunately, while there is no doubt that lean manufacturing increases productivity, efficiency, quality, and customers’ satisfaction by reducing wastes, there is a lack of research about the benefits of lean practices in relation to green manufacturing. The aim of the present work is to investigate the level of integration of green and lean manufacturing approaches, focussing specifically on the context of Saudi Arabia. As a result, a novel theoretical framework capable of combining the lean and green approaches within a synergetic environment, enhancing the former and mitigating the latter, is proposed. A survey was put together for assessing a number of hypotheses and validating the proposed framework. Qualitative analysis based on a survey conducted in different SME manufacturing companies in Saudi Arabia is presented. The statistical analysis of the collected data shows a clear trend that in Saudi Arabia, companies are starting to have a positive view about the integration of lean and green approaches implementation. The results highlighted higher maturity among the respondents with regard to the lean implementation, focussing on operational improvements. The improvements that can be attained with regard to environmental performance are coming next, and the framework proposed can help increase awareness among Saudi manufacturing SMEs.
Keywords: lean manufacturing; green manufacturing; lean-green manufacturing; sustainability